Therapeutic Frameworks in Integration Sessions in Substance-Assisted Psychotherapy: A Systematized Review - Thal, Sascha; Baker, Paris; Marinis, J.; Wieberneit, M.; Sharbanee, Jason; Bruno, R.; Skeffington, Petra; Bright, S. (2023)
Serotonergic psychedelics and related substances have been explored as potential adjuncts in substance-assisted psychotherapy (SAPT) for treating various disorders. SAPT can be divided into three phases: preparation, administration, and integration. Integration is commonly defined as the comprehension and effective application of insights from psychedelic experiences into everyday life. However, there is limited research regarding the most appropriate therapeutic approach during integration sessions in SAPT. In this article, we discuss the current evidence for different therapeutic frameworks for integrations sessions when serotonergic psychedelics and entactogens are used as adjuncts to psychotherapy. We conducted a systematized review of the literature following PRISMA guidelines and searched PsycINFO, MEDLINE, and Cochrane Library databases. The final synthesis included 75 clinical trials, mixed-methods investigations, treatment manuals, study protocols, quasi-experiments, qualitative investigations, descriptive studies, opinion papers, reviews, books and book chapters, published until November 11, 2022. The effects that various therapeutic approaches for integration sessions have on therapeutic outcome have not been investigated by means of rigorous research. Most of the available evidence we retrieved was not supported by empirical data, thus limiting any conclusive statements regarding appropriate therapeutic frameworks for integration sessions for SAPT. Current clinical studies have used a range of therapeutic frameworks with the majority drawing from the humanistic-experiential tradition. While integration is regarded as crucial for the safe application of SAPTHowever, there is currently an insufficient evidence base to suggest that any type of therapy is most effective for guiding integration sessions. Systematic investigation of different therapeutic frameworks for integration and additional therapy-related factors is needed.